The diet, habitat selection and body condition of impala AEPYCEROS MELAMPUS and nyala TRAGELAPHUS ANGASI in Zululand - Skinner, J.D. (John Dawson), 1932- (University of Pretoria, 2021)
Dissertation (MSc)--University of Pretoria, 1990.